Analisis Gerakan Remaja Masjid Pada Masjid Al Hikmah di Masa Milenial - Ageng saepudin kanda; Amelia Novianti Hermaela (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Teenagers are a group of people aged 13-17 years. Adolescence is a transition period for humans from children to adults, as we know, Generation Z has experienced a lot of changes, starting from losing a sense of social responsibility because they are busy with individual things, such as constantly playing with gadgets, no longer caring about activities. other social activities and even the surrounding environment. Before this goes too far, we as people who are aware of this must immediately become aware of the changes in our environment, as was done by the residents of Rt 01 in the Ciumbuleuit area, precisely at the Al-hikmah mosque, who started a movement to invite all teenagers who there to take part in several activities at the local mosque and revive the youth mosque movement in this millennial era. Increasing the activities of mosque youth so that they do not abandon activities that were previously very active in carrying out, we are carrying out this activity again to increase activities and advance work programs at the mosque, such as reciting the Koran regularly, welcoming the Isra Miraj event, one of them. To increase youth activities at the mosque again, we need a lot of hands to be able to bring teenagers back to the mosque by holding events at the mosque with things that are fun but still on the right track and not too excessive, then we can start with alternating activities such as doing activities outside the mosque. With so many teenagers taking part in this activity, the surrounding environment will be positively influenced, local residents will also take part in this activity by supporting the various event programs being held.